Quantitation of Residual Host Protein in Chicken Embryo-Derived Vaccines by Radial Immunodiffusion - O'Brien, Thomas C. (1971)
Quantitation of soluble residual host protein in chicken embryo-derived vaccines was performed rapidly, economically, and accurately by radial immunodiffusion.